2000
DOI: 10.4102/jsava.v71i2.684
|View full text |Cite
|
Sign up to set email alerts
|

Canine ehrlichioses : an update : review article

Abstract: The development of molecular biology techniques and methods for the isolation and growth of ehrlichias in tissue culture have greatly facilitated the study of these organisms. The available knowledge on ehrlichias is thus rapidly increasing and in this review recent findings on the epidemiology, transmission, clinical and laboratory signs of infection, diagnosis and treatment of canine ehrlichioses are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 82 publications
1
22
0
1
Order By: Relevance
“…This prevalence is similar to the 47% (148/310) [6] to 34% (50/146) [8] reported from Costa Rica in the only other PCR surveys of dogs in Central America, and these findings suggest the organism is prevalent in the region. Infections with E. canis cause canine monocytic ehrlichiosis with 80% of dogs developing prolonged thrombocytopenia [26,27]. We were unable to carry out hematological examinations on our study dogs but, despite the high likelihood that some were thrombocytopenic, all the surgeries were uneventful and no abnormal bleeding tendencies were noted.…”
Section: Resultsmentioning
confidence: 99%
“…This prevalence is similar to the 47% (148/310) [6] to 34% (50/146) [8] reported from Costa Rica in the only other PCR surveys of dogs in Central America, and these findings suggest the organism is prevalent in the region. Infections with E. canis cause canine monocytic ehrlichiosis with 80% of dogs developing prolonged thrombocytopenia [26,27]. We were unable to carry out hematological examinations on our study dogs but, despite the high likelihood that some were thrombocytopenic, all the surgeries were uneventful and no abnormal bleeding tendencies were noted.…”
Section: Resultsmentioning
confidence: 99%
“…51 In the severe form of disease, marked weight loss and emaciation, lymphadenopathy, pyrexia, and hemorrhagic disease are commonly observed. 50,53 Severe pancytopenia with nonregenerative anemia may also be detected; death results from extensive hemorrhage or secondary infection. 53 To the authors' knowledge, only 1 documented case of human infection with E canis has been reported in the medical literature.…”
Section: Ehrlichiosis In Animalsmentioning
confidence: 99%
“…50,53 Severe pancytopenia with nonregenerative anemia may also be detected; death results from extensive hemorrhage or secondary infection. 53 To the authors' knowledge, only 1 documented case of human infection with E canis has been reported in the medical literature. Ehrlichia canis was isolated from the blood of a healthy adult in Venezuela who reported close contact with an E canis-infected dog.…”
Section: Ehrlichiosis In Animalsmentioning
confidence: 99%
“…These primers amplify a 279 base pair DNA fragment. The E. canis and E. ruminantium PCR assays were performed as described previously (Savadye, Kelly & Mahan 1998;Peter et al 1995;2000). The specificity of the PCR assay was validated by amplifying a 350 bp DNA fragment from E. canis DNA but not from E. ruminantium DNA, a phylogenetically closely related species, using the 16S rDNA primers specific for detection of E. canis.…”
Section: Detection Of E Canis In Peripheral Blood Of Challenged Dogsmentioning
confidence: 99%
“…The chronic phase may be mild or severe depending on the strain of the parasite, age and breed of the animal, as well as the presence of concurrent disease. The chronic severe form is characterized by weight loss, pale mucous membranes, abdominal tenderness and bleeding tendencies with epistaxis reported in 30-50 % of the cases (Greene & Harvey 1984;Kelly 2000). It has been reported that German Shepherds are more prone to the chronic severe form of the disease, associated with specific and non-specific immunosupression induced by the E. canis infection (Huxoll, Amyx, Hemelt, Hildebrandt, Nims & Gouchenour 1972;Nyindo, Huxoll, Ristic, Kakoma, Brown, Carson & Stephenson 1980;Ristic & Holland 1993).…”
mentioning
confidence: 99%